Pengaruh Job Insecurity, Job Burnout, Konflik Peran Terhadap Stres Kerja Karyawan pada PT. Sinarmas Multifinance Cabang Kebumen - Astuti, Novia Rindi Puji; Rizana, Dani (LP3M Universitas Putra Bangsa, 2022)
This study aims to examine and analyze the effect of job insecurity, job burnout and role conflict on job stress. This research was conducted on employees of Pt.Sinarmas Multifinance Kebumen Branch. Data was collected by distributing questionnaires to 33 respondents of employees of PT.Sinarmas Multifinance Kebumen Branch. Data collection techniques by distributing questionnaires. The analysis used is validity test, reliability test, classic assumption test, multiple linear regression analysis test and coefficient of determination. The analysis technique used is using SPSS version 25 analysis program for Windows. The results obtained in this study indicate that the variables of job insecurity, job burnout, role conflict have a significant effect on job stress. The job insecurity variable has a significant effect on job stress, the job burnout variable has a significant effect on job stress, and the role conflict variable has a significant effect on job stress.